Communication skills (Back to the basics a five part series on business, 2000)
Presentations, reports, video conferences, e-mail, telephone calls—more than ever, excellent communication skills are a prerequisite for entry into all sorts of careers. This video provides guidance in strengthening both verbal and nonverbal communication. The importance of carefully targeting the message to be conveyed, minimizing outside distractions, listening attentively, and developing an awareness of body language are stressed.